Critical Design Features of Pre-Service Education Programs to Enhance Teacher Capacity to Effectively Work in Schools With Indigenous Students. Issue 2 (10th November 2014) - Labone, Elizabeth; Cavanagh, Patrick; Long, Janette
<x content-type="archive" xml:space="preserve">Abstract</x> For more than 3 decades governments and education systems have struggled to address the gaps in educational outcomes between Indigenous and non-Indigenous students. Over the past 10 years it has become increasingly apparent that central to redressing these gaps is the development of teachers who are able to effectively engage with Indigenous students, their families and communities. The introduction of National Professional Standards has increased the focus on the development of pre-service teachers' capacity to effectively teach Indigenous students. In 2008, the New South Wales Department of Education (DET) and four universities implemented an enhanced teacher training program (ETTP) that was delivered to final-year primary pre-service teachers. The success and continuing expansion of this program, coupled with the current national focus on building pre-service teachers' capacity to teach Indigenous students, suggests it is timely to detail the critical design features of, and rationale for, this program to inform and support development of similar programs within pre-service teacher education. The article reports on four critical elements of the program: knowledge and understanding of Aboriginal history and culture; effective cross-cultural communication skills; holistic understanding of Aboriginal education and strategies required for improving Aboriginal student outcomes; and appropriate pedagogy and classroom management strategies.